The impact of intellectual property on the community within Changlun - Che Din, Ahmad Shafiqee; Anuar, Herman Shah (2017)
This study aims to determine the impact of intellectual property on the community within Changlun. This study was held in Changlun. Intellectual property has become the common among industry practitioner when they want to deal business in the local and international market. Many companies have to face the challenge of equipping of equipping themselves with all the necessary measures in making business survived and sustained.There are two objectives in this study. First, to study about awareness of the company for the use of intellectual property rights. Second, to study about to see how intellectual property right can increase the productivity and competitiveness of the company in Changlun. Applying quantitative approach via questioner survey, the primary data in this study were analyzes using Statistical Package for Social Science (SPSS) version 22.The finding from the survey shown that company that realize about intellectual property right is more than the companies that do not take out.